2000
DOI: 10.1161/01.str.31.9.2163
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of the Loss of Distinction Between Gray and White Matter in Comatose Patients After Cardiac Arrest

Abstract: Background and Purpose-Anecdotal reports suggest that a loss of distinction between gray (GM) and white matter (WM) as adjudged by CT scan predicts poor outcome in comatose patients after cardiac arrest. To address this, we quantitatively assessed GM and WM intensities at various brain levels in comatose patients after cardiac arrest. Methods-Patients for whom consultation was requested within 24 hours of a cardiac arrest were identified with the use of a computerized database that tracks neurological consul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
133
3
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(156 citation statements)
references
References 27 publications
9
133
3
11
Order By: Relevance
“…Table 1 also presents data for ASPECTS-b, GWR, and QRA according to neurologic outcome. There was no difference in the GWR in the basal ganglia (P=0.101), centrum semiovale (P=0.970), and high convexity (P=0.774) between the 2 groups, and the mean GWR did not signifi- 14 However, the present study showed that GWR was not a significant outcome predictor for postcardiac arrest patients. This apparent discrepancy may be due to the early CT acquisition time frame (within 6 h, and usually around 2 h) in the present study, unlike in previous studies.…”
Section: General Demographicscontrasting
confidence: 69%
See 1 more Smart Citation
“…Table 1 also presents data for ASPECTS-b, GWR, and QRA according to neurologic outcome. There was no difference in the GWR in the basal ganglia (P=0.101), centrum semiovale (P=0.970), and high convexity (P=0.774) between the 2 groups, and the mean GWR did not signifi- 14 However, the present study showed that GWR was not a significant outcome predictor for postcardiac arrest patients. This apparent discrepancy may be due to the early CT acquisition time frame (within 6 h, and usually around 2 h) in the present study, unlike in previous studies.…”
Section: General Demographicscontrasting
confidence: 69%
“…12 Previous studies of post-cardiac arrest patients using brain CT have focused on the gray:white matter ratio (GWR). 13, 14 Few studies have focused on quantifying the extent of brain injury using brain CT. 15 The Alberta Stroke Program Early CT Score (ASPECTS) P ost-resuscitation status after cardiac arrest is a clinical model of hypoxia-ischemia injury. 1,2 Postresuscitation care including therapeutic hypothermia (TH) for neuroprotection is based primarily on recognition of brain damage.…”
mentioning
confidence: 99%
“…The most common type of neuroimaging studied has been cranial CT. Cranial CT studies can show widespread injury to the brain with changes in edema characteristics. 61,305 The acquisition of magnetic resonance imaging studies is challenging in critically ill patients because of restrictions on the type of equipment that can be placed in the room; however, this is becoming less problematic, and magnetic resonance imaging studies in the critically ill are increasingly being undertaken. Some limited studies have shown that diffuse cortical abnormalities in diffusion-weighted imaging or fluid-attenuated inversion recovery are associated with poor outcome.…”
Section: Neuroimaging and Monitoring Modalitiesmentioning
confidence: 99%
“…56 In a study of 25 comatose patients following CA for whom a CT scan was obtained within 48 hours, a difference in the gray matter to white matter ratio of <1.18 Hounsfield units at the level of the basal ganglia was predictive of death (0% FPR in 12 patients but with a wide confidence interval of 0%-22%). 57 Also, similar studies have had a low interrater reliability. 58 Brain MRI is frequently unremarkable despite other abnormal prognostic variables.…”
Section: Neuroimagingmentioning
confidence: 99%